1999
DOI: 10.1037/0022-006x.67.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of cognitive therapy and imaginal exposure in the treatment of chronic posttraumatic stress disorder.

Abstract: A randomized trial was performed in which imaginal exposure (IE) and cognitive therapy (CT) were compared in the treatment of chronic posttraumatic stress disorder (PTSD). Patients who continued to meet PTSD caseness at the end of a 4-week symptom-monitoring baseline period (n = 72) were randomly allocated to either IE or CT. There was a significant improvement in all measures over treatment and at follow-up, although there were no significant differences between the 2 treatments at any assessment. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
283
3
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(301 citation statements)
references
References 27 publications
10
283
3
5
Order By: Relevance
“…Speckens and colleagues (2006) found that initial PTSD symptom severity (but not initial anxiety, depression, dissociation or self blame) was associated with the degree of change in intrusive memories following imaginal reliving in the context of a cognitive-behavioral treatment. Tarrier et al (1999) found that patients who deteriorated were rated as less motivated by their therapists than were patients who improved. These studies suggest that certain individuals may be more likely to improve and others likely to show some deterioration.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Speckens and colleagues (2006) found that initial PTSD symptom severity (but not initial anxiety, depression, dissociation or self blame) was associated with the degree of change in intrusive memories following imaginal reliving in the context of a cognitive-behavioral treatment. Tarrier et al (1999) found that patients who deteriorated were rated as less motivated by their therapists than were patients who improved. These studies suggest that certain individuals may be more likely to improve and others likely to show some deterioration.…”
Section: Introductionmentioning
confidence: 96%
“…Few studies have focused on this topic. However, across PTSD treatment studies the following developments have been found in some degree: worsening of psychiatric symptoms among some individuals that is not generally indicative of poorer long-term outcomes (Foa et al, 2002;Tarrier et al, 1999 ); and individual differences leading to variations in treatment response (Hembree et al, 2004;Morrisey et.al., 2005 ;Speckens et al, 2006 ;Tarrier et al, 1999 ). These developments make clear that further investigation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…With PTSD, the core components of exposure therapy programs are imaginal exposure, or repeated recounting of the traumatic memory, and in vivo exposure, the repeated confrontation with trauma-related situations and objects that evoke excessive anxiety. Across several well-conducted studies, between 40 and 87% of participants no longer meet criteria for PTSD after 9-15 sessions of exposure therapy alone (eg, Foa et al, 1991(eg, Foa et al, , 1999Marks et al, 1998;Paunovic and Ost, 2001;Resick et al, 2002;Tarrier et al, 1999;Taylor et al, 2003) and exposure therapy combined with either stress inoculation training (Foa et al, 1999) or cognitive therapy (eg, Bryant et al, 2003b;Marks et al, 1998;Paunovic and Ost, 2001). By comparison, less than 5% of participants lose the PTSD diagnosis after a comparable period of time with no intervention (ie, waitlist control) and 10-55% of participants after receiving an active control treatment such as supportive counseling (Bryant et al, 2003b;Foa et al, 1991) or relaxation (Marks et al, 1998;Taylor et al, 2003) lose the PTSD dianosis.…”
Section: Exposure Therapymentioning
confidence: 99%
“…With PTSD, the goal of cognitive therapy is to teach the patient to identify trauma-related or symptom-related irrational or dysfunctional beliefs that may influence his/ her response to a situation and lead to intense negative emotion (Marks et al, 1998;Tarrier et al, 1999). The patient is taught to challenge these thoughts or beliefs in a logical, evidence-based manner.…”
Section: Cognitive Therapymentioning
confidence: 99%
See 1 more Smart Citation